How did the Affordable Care Act Medicaid Expansion Affect Coverage and Access to Care for Low-Income Parents Who Were Eligible for Medicaid Before the Law Was Passed? - Stacey McMorrow PhD; Genevieve M. Kenney PhD (SAGE Publishing, 2021)
We use the National Health Interview Survey from 2010 to 2017 and a difference-in-differences approach to assess the impact of the Affordable Care Cct (ACA) Medicaid expansion on coverage and access to care for a subset of low-income parents who were already eligible for Medicaid when the ACA was passed. Any gains in coverage would typically be expected to improve access to and affordability of care, but there were concerns that by increasing the total population with coverage and thereby straining provider capacity, that the ACA would reduce access to care for individuals who were already eligible for Medicaid prior to the passage of the law. We found that the expansion reduced uninsurance among previously eligible parents by 12.6 percentage points, or a 40 percent decline from their 2012-2013 uninsurance rate. Moreover, these effects grew stronger over time with a 55 percent decline in uninsurance 2 to 3 years following expansion. Though we identified very few statistically significant impacts of the expansion on affordability of care, descriptive estimates show substantial declines in unmet needs due to cost and problems paying family medical bills. Descriptively, we find no significant increases in provider access problems for previously eligible parents, and very limited evidence that the Medicaid expansion was associated with more constrained provider capacity. Though sample size constraints were likely a factor in our ability to identify impacts on access and affordability measures, our overall findings suggest that the ACA Medicaid expansion positively affected our sample of low-income parents who met pre-ACA Medicaid eligibility criteria.